2018
DOI: 10.5606/tgkdc.dergisi.2018.14841
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of truncus arteriosus repair with bovine jugular vein conduit

Abstract: ÖZAmaç: Bu çalışmada Rastelli tipi trunkus arteriyozus olan hastalarda trunkus arteriyozus tamirinin sonuçları değerlendirildi.Çalışma planı: Ocak 2011 -Mart 2017 tarihleri arasında 13 hastaya (7 erkek, 6 kadın; medyan yaş 37 gün; dağılım, 16-60 gün) Contegra kondüiti kullanılarak trunkus arteriyozus tamiri yapıldı. Ameliyat öncesi tanı sekiz hastada trunkus arteriyozus tip 1 (Edwards-Collett), üç hastada tip 2, bir hastada tip 3 ve bir hastada tip 4 idi. Ameliyat için kullanılan Contegra kondüitleri 14 mm (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, one center reported significant early fibrous epidermis formation at the distal anastomosis, as well as significant dilation and regurgitation of the conduit in the case of pulmonary hypertension or distal obstruction of the aforementioned distal anastomosis ( 87 ). Some studies have shown that BJV conduits have good medium-term durability, but have not been compared with the homograft or other types of conduits ( 88 , 89 ). Therefore, this conduit will require further observation at longer follow-up times to clarify the differences in performance compared to equivalent sized cryopreserved homograft ( 43 ).…”
Section: Xenograft Valved Conduits and Other Possible Alternativesmentioning
confidence: 99%
“…In addition, one center reported significant early fibrous epidermis formation at the distal anastomosis, as well as significant dilation and regurgitation of the conduit in the case of pulmonary hypertension or distal obstruction of the aforementioned distal anastomosis ( 87 ). Some studies have shown that BJV conduits have good medium-term durability, but have not been compared with the homograft or other types of conduits ( 88 , 89 ). Therefore, this conduit will require further observation at longer follow-up times to clarify the differences in performance compared to equivalent sized cryopreserved homograft ( 43 ).…”
Section: Xenograft Valved Conduits and Other Possible Alternativesmentioning
confidence: 99%